Perlindungan Hukum Tenaga Kesehatan (Penata Anestesi) Setelah Terbitnya Undang-Undang Kesehatan Nomor 17 Tahun 2023 - Wahyudiono, Gunawan; Ismono, Joko; Daim, Nuryanto A. (Law and Humanity, 2024)
Anesthesiology services and intensive therapy in hospitals are part of health services that are developing rapidly in line with improvements in science and technology in the field of anesthesia. Law no. 17 of 2023 concerning Health provides a glimmer of hope that there will be a solution to meet the needs of specialist/subspecialist doctors in various regions. The formation of Law Number 17 of 2023 concerning Health has proven to cause obstacles. The regulations tell how hospitals as an extension of the minister, provincial government and district/city government should act, how to respond and what sanctions there will be. However, the existence of anesthesia practitioners who practice without STRPA and SIPPA is an indication that the law is not working optimally in society.